2020
DOI: 10.1007/s10453-020-09651-x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological air quality in pharmacies and an antibiotic resistance profile of staphylococci species

Abstract: The air in public facilities contains microorganisms which may cause a wide variety of clinical syndromes in humans. This is particularly important in primary healthcare units, where patients with reduced immunity and staff are directly exposed to microbial pathogens. Air samples were collected from dispensing areas (customer areas) of five pharmacies using MAS-100 air sampler. The concentration of particular groups of microorganisms was determined with the use of selective media. The taxonomic analysis of man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…(Madhwal et al, 2020 ) monitored the bioaerosols near Bus station and an almost similar trend was recorded in all the seasons. Aspergillus, Penicillium , and Cladosporium were the most dominant fungi; however, Micrococcus, Staphylococcus, , and Bacillus were the most dominant bacterial genera (Madhwal et al, 2020 ), and the same results were shown in the monitoring of indoor air of pharmacy (Jankowiak et al, 2020 ). Fungal aerosols started declining from July–August, which may be due to increased soil moisture and hence, decreased resuspension of fungi in these months (Fan et al, 2017 ; Rathnayake et al, 2017 ).…”
Section: Resultsmentioning
confidence: 75%
“…(Madhwal et al, 2020 ) monitored the bioaerosols near Bus station and an almost similar trend was recorded in all the seasons. Aspergillus, Penicillium , and Cladosporium were the most dominant fungi; however, Micrococcus, Staphylococcus, , and Bacillus were the most dominant bacterial genera (Madhwal et al, 2020 ), and the same results were shown in the monitoring of indoor air of pharmacy (Jankowiak et al, 2020 ). Fungal aerosols started declining from July–August, which may be due to increased soil moisture and hence, decreased resuspension of fungi in these months (Fan et al, 2017 ; Rathnayake et al, 2017 ).…”
Section: Resultsmentioning
confidence: 75%
“…The antibiotic resistance profiles of A. hydrophila isolated from indoor and outdoor air have never been described in the literature, because this bacterial species is not considered in studies monitoring the microbiological quality of indoor and outdoor air. It should also be noted that indoor air microbiota comprise mainly Grampositive bacteria, whereas Gram-negative bacteria, including A. hydrophila, are sporadically detected [7,42,43]. Only a single species of Gram-positive bacteria was identified in a study analyzing the antibiotic resistance of strains isolated from bioaerosols in an office building in Gliwice, Poland.…”
Section: Discussionmentioning
confidence: 99%
“…They indicated a high microbiological contamination level in the hospital air. Jankowiak et al ( 2020 ) measured microbiological contamination in dispensing areas in pharmacies in hospital buildings. The results showed that the highest heterotrophic bacteria and staphylococci concentrations recorded were in pharmacies.…”
Section: Introductionmentioning
confidence: 99%